(untitled) (International Journal of Physiotherapy, 2016)
Background: Premenstrual syndrome is a current condition characterized by troublesome symptoms as tension, irritability, depression, headache, anxiety and loss of self-control, so the aim of this study was to investigate the effect of foot reflexology augmented with relaxation training on premenstrual syndrome in adolescent females. Methods: A sample of 50 volunteers, virgin females diagnosed as premenstrual syndrome was selected from the students of Faculty of Physical Therapy, Cairo University. Their age was ranged between 19 to 23 years with mean value of (21.53±2.27 yrs) and BMI was ≤28 Kg/m² with mean value of (24.04±2.41 Kg/m²).A detailed medical history was obtained to screen other pathological conditions that may affect the results. Females were randomly assigned into two equal groups. Group (A) consisted of 25 subjects who received foot reflexology in addition to relaxation training techniques twice a week for 8 weeks. Group (B) consisted of 25 patients, who received relaxation training techniques only twice a week for 8 weeks. Assessment of all subjects in both groups was carried out before and after the treatment program through heart rate, respiratory rate in addition to plasma cortisol level and daily symptoms report chart. Results: Showed a statistical highly significant decrease (p<0.001) in heart rate, respiratory rate, plasma cortisol level as well as daily symptoms report score in group (A) while there was a statistical significant decrease (p<0.05) in all variables in group (B). Conclusions: Adding foot reflexology to relaxation training had a great positive effect on premenstrual syndrome in adolescent females than relaxation training only.